Gambaran Gratitude Pasca Kematian Pasangan pada Dewasa Madya dengan Resiliensi Tinggi - Rachel Putri Kartikasari; Wahyuni Kritinawati (Institut Nalanda, 2026)
The death of a spouse in middle adulthood can lead to changes in roles, increased responsibilities, and psychological as well as social challenges that affect the process of adjustment. In facing these circumstances, resilience is an important capacity that helps individuals endure and recover from experiences of grief. In addition, gratitude plays a significant role in enabling individuals to interpret the loss in a more adaptive manner. Therefore, this study aims to describe gratitude among middle-aged adults with high resilience following the death of a spouse. This research employed a qualitative approach using a phenomenological method. Participants were selected through purposive sampling, supported by quantitative screening to identify middle-aged adults with high levels of resilience. Data were collected through interviews and observations. The findings indicate that gratitude among middle-aged adults after the loss of a spouse is reflected in four main aspects and is influenced by factors such as well-being and religiosity. These findings suggest that gratitude helps individuals accept their loss and adaptively rebuild their lives following bereavement.